Thermal analysis and thermography observation of stainless-steel ice cubes - Luthfi Luthfi; Azhar Azhar; Zuhaimi Zuhaimi; Syamsuar Syamsuar; Sumardi Sumardi (Politeknik Negeri Lhokseumawe, 2023)
Alternative products for water ice cubes have long been sought due to the spread of waterborne diseases and microplastic contamination, as they are often made from unhygienic water sources. Recently, stainless-steel ice cubes have been considered as one of the best alternatives, and they have been very popular in marketplaces, although very few studies found in the literature that have investigated their potential in replacing water ice cubes. In this study, the thermal performance of stainless-steel ice cubes will be explored experimentally using a combination of an Arduino microcontroller equipped with DS18B20 thermocouple sensors and a HIKMICRO B20 thermal camera with the aim to find out how good stainless steel ice cubes for cooling food and beverages. The time evolution of water temperature in glasses filled with stainless-steel cubes of various brands is compared with that of water ice cubes. The temperature field obtained from thermal images is used to further observe the overall temperature of water in the glass. Leeseph stainless-steel ice cubes are found to have thermal performance comparable to water ice cubes, while SSGP ice cubes can retain lower temperatures for a longer time compared with other ice cubes. The effect of the number of ice cubes (N), the volume of water (V), and the average diameter of the glass used (D) are also investigated. At 1 ≤ N ≤ 4, the larger number of ice cubes used are found to lower the minimum temperature, and to decrease the minimum time, while at 150 ml ≤ V ≤ 300 ml, the larger amount of water used are observed to increase the minimum temperature and to increase the minimum time, . At 53 mm ≤ D ≤ 66 mm, larger glass diameter used are found to increase both the minimum temperature, and the minimum time